SPIRITUALITAS TANPA AGAMA: POTRET PERKEMBANGAN RELIGIUSITAS DI BARAT - Fahmy Farid Purnama (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
This paper will disscuse the development of religiosity in the Westillustrated by Lenny Bruce that ‘every day people are straying away from the church and going back to God.’ The social phenomenon marked a paradigmatic shift that is very significant in religiosity awareness. The paper will also examine the development of spiritual stretching the Western secular society which is reflected in New Age Movement and New Religion Movements.